John Heartfield : laughter is a devastating weapon ; his original photomontages and printed matter from Akademie der Künste Berlin and the David King Collection at Tate Modern (Tate Publishing, 2015)
"Born in Berlin in 1891, John Heartfield, along with George Grosz, is widely considered to have invented photomontage, a technique of cutting up and manipulating photographs. During the 1930s Heartfield produced some of the most visually arresting and politically hard-hitting artwork of the twentieth century, appropriating the widely circulated propaganda of the time to create a biting critique of contemporary politics. This lavishly illustrated, large-format survey of his work, the most authoritative yet published, draws on the superlative collections of the Academie der Kunst, Berlin, and the David King collection at Tate Modern. Including more than 150 full-colour reproductions of Heartfield's powerful work, both in its original and printed forms, as well as documentary photographs and recollections from Heartfield's surviving family members, the book features a lively introduction by David King, as well as illuminating short texts on many of the works. Heartfield's astonishing visual broadsides, aimed at the abuse and misuse of power, and part of his lifelong wish to create a fairer and more peaceful world, are every bit as relevant and cutting-edge today as when they were first published."--Publisher's description